Globalization - Today, Tomorrow - Kent G. Deng (IntechOpen, 2010)
This is a collective volume on present-day globalisation with nine chapters from authors of several academic disciplines. It covers wide aspects, ranging from the nature, impact, challenges and implications of globalisation to responses from a country or community when facing globalisation today or tomorrow. Policy suggestions are also made. This book will hence help the reader to understand the currently debated issues.
English
Keywords: Education; Globalization; Social Sciences and Humanities; Management and Economics; Business